Analysis of the 2020 President's Budget - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2020)
The government budget reflects the government's spending priorities. It is deemed important to assess whether the priorities as outlined in the proposed 2020 President's Budget are consistent with the policy pronouncements of the current administration. In this light, the study examines whether budget allocation is consistent with the priorities that the government identified in its various policy pronouncements. It also evaluates the overall fiscal picture as projected in the proposed budget and its consistency with the macroeconomic assumptions. In addition, it examines the national revenue program, which together with the national expenditure program indicates the overall fiscal health in the 2020. The budget analysis indicates the high spending priority given to social services sector and economic services sector that is consistent with the policy pronouncements of the government. Nevertheless, the budget cut in the health sector needs further inquiry.
Keywords: 330; President's Budget; National Expenditure Program